A clinical audit of female urinary incontinence at a urogynaecology clinic of a tertiary hospital in Durban South Afric - Tunde Dehinbo; Suran Ramphal; Jagedisa Moodley (South African Medical Association, 2015)
Background. Urinary incontinence (UI) is a common condition with an increasing prevalence worldwide. Although it is not a life-threatening condition, it can be very disabling.Objective. To describe the clinical profiles, risk factors, diagnosis, treatment and clinical outcomes of women with different subtypes of UI who attended a tertiary hospital in Durban, South Africa.Methods. A retrospective chart review was performed. A structured data form was used to obtain the relevant information.Results. Seven hundred and fifty-eight of 945 charts with a diagnosis of UI were analysed. Stress urinary incontinence (SUI) was the most common subtype of UI (30%). The mean (standard deviation (SD)) age was 50.9 (15.2) years; mean (SD) parity 2.8 (1.4) and mean (SD) body mass index 29.2 (5.3) kg/m2. Indians (n=366, 48.3%) were the predominant racial group; black Africans constituted 32.7% (n=248). Mid-urethral tape was the preferred surgical treatment for SUI (n=134, 62.0%). Urge UI was treated mainly with pharmaceutical agents (n=138, 74.2%) with physiotherapy as adjunctive therapy. Urogenital fistulas were repaired via laparotomy (n=42, 53.9%) and vaginally (n=25, 32%). Mid-urethral tapes and Burch colposuspension had success rates of 97% and 83.3%, respectively. Both laparotomy and vaginal fistula repairs had success rates of 95%.Conclusions. Stress UI was the most common subtype of UI observed in this study. Patients were predominantly Indians and overweight or obese. The majority of patients with urogenital fistulas were black Africans. Surgical outcomes at our centre were in keeping with those in international reports.